Development and characterisation of glucosamine sulphate magnetic nanoparticles for rheumatoid arthritis chemotherapy. (1st November 2020) - Subbiah, Latha; Palanisamy, Selvamani; Thimiri Govinda Raj, Deepak B.
Abstract : Rheumatoid arthritis (RA) is an autoimmune disease that principally attacks synovial joints. RA also cause inflammation in the joints and associated regions. There is an unmet medical need for RA as well as for the targetted drug delivery of anti‐rheumatic drugs to improve its efficacy at a much lower doses while decreasing its side effects. Hence, in this Letter, the authors report the development and characterisation of glucosamine sulphate magnetic nanoparticles for magnetically targetted RA chemotherapy.